Contraceptive use at the time of and after an ectopic pregnancy: a retrospective cohort study. (3rd March 2020) - Nordström, Fanny; McTaggart, Julia; Melander, Emma; Altman, Daniel; Kopp Kallner, Helena
Abstract: Objectives: Approximately, 1–2% of all pregnancies are ectopic; 25% of unintended pregnancies are conceived despite the use of contraception. The primary objective of our study was to explore the proportion of ectopic pregnancies (EPs) that were conceived during contraceptive use among women in Stockholm County. Secondary objectives were to establish the prevalence of contraceptive methods used at the time of EP and the intended contraceptive method after treatment completion. Methods: We performed a retrospective cohort study of 1180 women diagnosed with and treated for EP between 1 December 2013 and 30 April 2017 at all hospitals in Stockholm County. Demographic variables and contraceptive use before and after treatment were noted. Exclusion criteria were uncertainty about the diagnosis of EP in the patient records and planned treatment/follow-up outside Stockholm County. Results: A total of 222/1180 (18.8%) EPs were conceived during known contraceptive use. A total of 112/222 (50.5%) women with known use of contraception at the time of conception discontinued contraceptive use and 81/857 (9.5%) women with no prior use of contraception initiated contraceptive use. Among the 857 women, 520 (60.7%) expressed a desire to conceive. Results were compared using the Mann–Whitney U test or Fisher's exact test as appropriate. Conclusion: EP occurring during use of contraception is an unexplored problem. Contraceptive use decreased in women who were using contraception at the time of EP conception, leaving these women at risk of a subsequent unintended pregnancy. There should be more focus on contraceptive use after treatment for EP, in order to preserve fertility.